Bilateral pneumothorax: the cause of hypoxia during endoscopic retrograde cholangiopancreatography - Saeed Madani; Rohallah Taghavi; Mohammad saiidi; Jamshid vafaeimanesh (Babol University of Medical Sciences, 2021)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) is recognized as a significant diagnostic and therapeutic procedure for the administration of different pancreatic and biliary problems. This procedure runs a considerable risk of complications despite its substantial safety. The rate of significant inconveniences is reported to range from 5.4% to 23.0% and the general mortality from 0.1 to 1%. Post-ERCP pneumothorax is an uncommon complication that is usually underestimated Case Presentation: In the present study, we report a 65-year-old woman who develops hypoxemia during the ERCP. Based on the obtained results, it was revealed that this patient had perforation-related bilateral pneumothorax and hypoxemia. Conclusion: Based on the obtained results, it was revealed that this patient had perforation-related bilateral pneumothorax and hypoxemia.